IMPLEMENTASI NILAI-NILAI PANCASILA DALAM POLA PEMBINAAN SANTRI KELAS XI A (PUTRA) MA AL-JAUHAREN DI PONDOK PESANTREN AL-JAUHAREN KEL. TANJUNG JOHOR KEC. PELAYANGAN KOTA JAMBI - H., Pahmi; Maulia, Siti Tiara; Ekawarna, Ekawarna (Academy of Education Journal, 2023)
The implementation of Pancasila values in Pondok Pesantren must be optimal to form ideological, nationalist, and religious santri, and prevent deviant behavior. It helps santri become independent, responsible, and improve problem-solving and decision-making skills. The great influence of boarding school administrators and coaches affects how santri practice the values of Pancasila. Research at the Al-Jauharen Islamic Boarding School in Jambi City used descriptive qualitative data methods with observation, interviews, and documentation. Data validity was tested using triangulation of techniques, data sources, and time. The results showed that the implementation of Pancasila values in class XI A male students at the Al-Jauharen Islamic Boarding School has been carried out thoroughly through formal and non-formal education. The constraints of the coach include a less supportive environment, the diverse characteristics of the students are difficult to form conformity with the values of Pancasila, and the students' lack of understanding of these values.